Sense of Community Mediating Between Age-Friendly Characteristics and Life Satisfaction of Community-Dwelling Older Adults - Au, Alma; Lai, Daniel W. L.; Yip, Ho-ming; Chan, Stephen; Lai, Simon; Chaudhury, Habib; Scharlach, Andrew; Leeson, George (Frontiers in Psychology, 2020)
The growth of age-friendly community initiatives underscores a paradigmatic shift from the individual to the community, addressing dynamic transactions between people and their environment they are living in. The purpose of the present study is to address the gap in existing research by examining the psycho-social effects of the sense of community in mediating between WHO domains of age-friendliness and the life satisfaction of older adults. Data were obtained from eight hundred and ninety-eight participants in Hong Kong. Path analysis was conducted. Two AFC domains, social participation as well as community support/ health services, were found to be associated with life satisfaction. Sense of community was found to mediate between these two domains and life satisfaction. The implications of these findings are discussed with reference to developing opportunities in social participation of older adults and enhancing community/ health support services in the context of developing sustainability in the community.